2017
DOI: 10.7555/jbr.31.20160108
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation, inflammatory response and lung injury during one lung ventilation in rabbits using inspired oxygen fraction of 0.6 vs. 1.0

Abstract: Maintaining adequate oxygenation during one-lung ventilation (OLV) requires high inspired oxygen fraction (FiO2). However, high FiO2 also causes inflammatory response and lung injury. Therefore, it remains a great interest to clinicians and scientists to optimize the care of patients undergoing OLV. The aim of this study was to determine and compare oxygenation, inflammatory response and lung injury during OLV in rabbits using FiO2 of 0.6 vs. 1.0. After 30 minutes of two-lung ventilation (TLV) as baseline, 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Previous studies showed hyperoxia during OLV increased the levels of inflammation and oxidative stress, leading to a higher risk of complications after surgery ( 21 , 22 ). Our previous research studied the benefits of lower FiO 2 in lowering inflammation, oxidative stress, and lung injury ( 8 , 9 ). Although higher PEEP increased oxygenation, the levels of inflammation also increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed hyperoxia during OLV increased the levels of inflammation and oxidative stress, leading to a higher risk of complications after surgery ( 21 , 22 ). Our previous research studied the benefits of lower FiO 2 in lowering inflammation, oxidative stress, and lung injury ( 8 , 9 ). Although higher PEEP increased oxygenation, the levels of inflammation also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Although high fraction of inspiration O 2 (FiO 2 ) (1.0) improved oxygenation ( 5 ), the following higher levels of inflammation remarkably raised acute respiratory distress syndrome (ARDS) risk, leading to increased postoperative mortality ( 6 , 7 ). Several reports have shown the independent risk factors for ARDS are high FiO 2 and airway pressure, as well as prolonged OLV ( 6 - 8 ), and maximizing the use of minimum FiO 2 under adequate oxygenation is the current recommended strategy for protective ventilation ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTA1 is part of the nuclear remodeling and deacetylation (NuRD) complex that ubiquitously regulates the expression of genes that enhance the migration and invasion of malignant cells [7]. Upregulation of MTA1 has been reported in a variety of cancers, including colorectal carcinoma [8,9], gastric cancer [10], and laryngeal squamous carcinoma [11]. In lung cancer, MTA1 has recently been identified as a prognostic biomarker that is associated with the poor prognosis in patients with lung cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoventilation may cause hypoxia and ischemic damage and destruction of cells. In the process of restoring blood supply, it can also increase the damage of cells, cause pathological and physiological changes in the lungs, and induce ischemia-reperfusion injury, and hypoxemia followed by acute inflammatory reactions and oxidative stress reactions, causing acute injury to multiple organs throughout the body (3,4). Studies have shown that prolonged OLV and mechanical stimuli resulting from surgery can lead to the activation of inflammatory cells in patients, and the release of inflammatory factors may cause increased inflammatory reactions in the lungs and increased lung injury in patients, which in turn increase the risk of postoperative death (5).…”
Section: Introductionmentioning
confidence: 99%